Natural dye modification of polyethylene oxide: optical characterization and dielectric enhancement - Shujahadeen B. Aziz; Dana S. Muhammad; Sewara J. Mohammed; Daron Q. Muheddin; Shakhawan Al-Zangana; Ahang M. Hussein; Ary R. Murad; Govar H. Hamasalih; Samir M. Hamad; Dilshad Shaikhah (Journal of Materials Science: Materials in Engineering)
Abstract This study explores the optical properties of polyethylene oxide (PEO) modified with natural dye extracted from hollyhock (HH) flowers. This study is a green chemistry approach to reduce the optical band gap of PEO polymer. The UV-vis analysis of the HH dye demonstrated absorption spanning from UV to visible regions of the electromagnetic spectrum. Fourier transform infrared spectroscopy (FTIR) analysis identified significant transmittance bands linked to the OH, NH, and C = O functional groups of HH dye. The shifts and intensity changes in FTIR bands of the doped PEO indicate interactions between PEO and HH dye functional groups. A shift was observed in the absorption edge from 5.6 eV for clean PEO to 2.6 eV for dye-doped film. The addition of HH dye resulted in an increase in the optical dielectric constant, suggesting a rise in the localized density of energy states within the forbidden band separating the valence bands (VBs) and conduction bands (CBs). The refractive index of doped PEO was found to be 1.73 which is greater than that of pure PEO (1.27). The optical band gap determination based on Tauc’s model was found to decrease from 5.3 eV for pure PEO to 2.4 eV for dye-doped PEO film. The study identified the dominant type of electron transition, a complex topic in condensed matter physics involving electrons crossing the band gap.